Mathematics

Question

Consider this quadratic equation.

x2 + 1 = 2x – 3

Which expression correctly sets up the quadratic formula?
Consider this quadratic equation. x2 + 1 = 2x – 3 Which expression correctly sets up the quadratic formula?

2 Answer

  • Answer:A

    Step-by-step explanation:

  • The equation that best set up the quadratic formula is [tex]x = \frac{ -(-2) |+-| \sqrt{(-2)^2-4(1)(4)} }{2(1)}[/tex].

    Hence, option A is the correct answer.

    What is a Quadratic Equation?

    Quadratic equation is simply an algebraic expression of the second degree in x. Quadratic equation in its standard form is;

    ax² + bx + c = 0

    Where x is the unknown

    Using the quadratic formula

    x = (-b±√(b² - 4ac)) / (2a)

    Given that;

    x² + 1 = 2x – 3

    First we re-arrange the the equation.

    x² + 1 = 2x - 3

    x² - 2x + 1 + 3 = 0

    x² - 2x + 4 = 0

    Hence;

    • a = 1
    • b = -2
    • c = 4

    Next we input this values into the quadratic formula

    x = (-b±√(b² - 4ac)) / (2a)

    x = (-(-2)±√((-2)² - 4(1)(4))) / (2(1))

    [tex]x = \frac{ -(-2) |+-| \sqrt{(-2)^2-4(1)(4)} }{2(1)}[/tex]

    The equation that best set up the quadratic formula is [tex]x = \frac{ -(-2) |+-| \sqrt{(-2)^2-4(1)(4)} }{2(1)}[/tex].

    Hence, option A is the correct answer.

    Learn more about quadratic equations here: brainly.com/question/1863222

    #SPJ5